The protective role of black tea extract against indomethacin-induced toxicity in the prostate gland of rats - Ishwar B Bagoji; G A Hadimani; R S Bulagouda; M K Qureshi; Kusal K Das (Wolters Kluwer Medknow Publications, 2020)
Introduction: Indomethacin (NSAID) is an endocrine-disrupting chemical (EDC) that has been demonstrated to induce alterations in reproductive organs while Black Tea Extract (BTE), an antioxidant, is capable of protecting against EDC-induced alterations. Aims & Objectives: The current study was designed to investigate the role of black tea extract on biochemical, hormonal, and histological changes in the prostate of male Wister rats treated with indomethacin drugs. Materials and Methods: Adult rats were divided into four groups (n = 6/group); Group I (control); Group II (indomethacin, 5 mg/kg b.wt.; i.p.); Group III (BTE, 2.5 g tea leaf/dL of water, i.e., 2.5% of aqueous BTE, orally) and Group IV (indomethacin + BTE) for 21 successive days. Sperm Count, Motility, Prostate-Specific Antigen (PSA), Testosterone levels, total protein, GSH, CAT, and MDA levels and the histopathological aspects of the prostate gland were studied. Statistical Analysis: Statistical comparisons were performed using the one-way ANOVA, followed by post-hoc t-test. Results: Indomethacin treated rats "Group" II exhibited a significant (P≤0.05) declining in the sperm count, motility PSA and testosterone concentration, total protein, GSH concentration, and CAT activity. A high concentration of MDA levels in the serum indicated the appearance of oxidative stress status in the Wister rats. The indomethacin had a significant impact on the weight, and histopathology of glandular "acini" and excretory "ducts" revealed hyperplasia, intra-luminal budding of epithelia as well as tubular atrophy. Conclusion: Administration of black tea extract abrogated the toxic effect induced by indomethacin on the prostate gland.